Penelitian Penimbunan (Land Fill) Baterei Kering Bekas - Sri Pudji Rahayu; Dwinna Rahmi; Ukar Tarwiyono (Jurnal Kimia dan Kemasan, 1998)
Disposal of ex-dry cell is one of some waste which is potential for environmental pollution, because dry cell containt heavy metal and other material which is characteristic toxic.This research show the impact disposal of this dry cell. Result from lechate test show that heavy metal which is contained in dry cell shall be leachate in water, moreover in acid condition.